Peran Gizi Olahraga dalam Meningkatkan Power dan Daya Tahan Atlet Bola Voli: Sebuah Tinjauan Literatur - Sahabuddin (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Modern volleyball requires complex physical capacities, particularly explosive power and match-specific endurance that are closely associated with the performance of anaerobic and aerobic energy systems. Increasing performance demands indicate that training programs alone are insufficient to produce optimal athletic performance; therefore, sports nutrition strategies become a crucial component in supporting athletes’ physiological adaptation processes. The research problem addresses how sports nutrition contributes effectively to improving the power and endurance of volleyball athletes based on recent scientific evidence. This study aims to systematically analyze the contribution of sports nutrition to enhancing the physical capacity of volleyball athletes through a scientific literature review approach. The research method employs a Systematic Literature Review (SLR) using the PRISMA framework to examine articles indexed in Scopus and SINTA published between 2015 and 2024. The identification process yielded 312 articles, followed by a rigorous screening and eligibility assessment that resulted in 22 articles meeting the inclusion criteria, with 10 core studies analyzed in depth to obtain a synthesis of relevant scientific findings. The results indicate that carbohydrate periodization of 6-8 g/kg body weight per day contributes to an improvement in vertical jump performance by approximately 3-6%, while optimal protein intake of 1.6-2.2 g/kg body weight per day increases peak power by about 4-8%. Creatine monohydrate supplementation of 3-5 g per day has been shown to enhance explosive power by 5-12%, whereas beta-alanine supplementation improves anaerobic work capacity by 8-14%. Hydration strategies and carbohydrate regulation also contribute to an increase in VO₂max by 2-5% and reduce the fatigue index by 6-10%. The findings confirm that sports nutrition functions as an essential mediator between training stimuli and the neuromuscular as well as metabolic adaptation responses of athletes. The novelty of this study lies in its conceptual synthesis that positions nutritional periodization as an evidence-based integrative strategy for sustainably optimizing the power and endurance of volleyball athletes.